Development of Product-Based Job Sheet as Instructional Media in Vocational Education - Rini Widyastuti; Iga Setia Utami (Universitas Negeri Makassar, 2018)
The purpose of this research is to produce a product-based job sheet that can be used as an instructional media on practicum activities. In this study also tested the validity of the job sheet developed. The research method used is research development with a 4D model consisting of define, design, development and disseminate. The research instrument used is a validation sheet consisting of content validation, format, and presentation of the job sheet which is analyzed by descriptive analysis technique. The results showed that 1) the product-based job sheet developed was highly valid on the content/content aspects, 2) the product-based job sheet developed valid on the aspect of the format, and 3) the product-based job sheet developed was valid in the presentation aspect. Based on the results of the study can be concluded that the product-based worksheet developed valid for use in Object Oriented Programming subject.